Pengaruh Penambahan Variasi Fraksi Massa Serbuk Cangkang Kelapa Sawit (PKS) pada Sifat Mekanis Komposit Hibrid Fiberglass–Epoxy - Vina Nanda Garjati; Vika Rizkia; Dewin Purnama; Tia Rahmiati; Amalina Shomami (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The demand for renewable energy sources in Indonesia continues to rise in line with national energy transition efforts. Wind energy represents a significant but underutilized potential, yet its development is hampered by high investment costs, particularly in manufacturing wind turbine blades that rely on expensive composite materials. This research aims to identify more economical and sustainable material alternatives without compromising the necessary mechanical strength. Hybrid composites were developed by combining fiberglass and palm kernel shell (PKS) powder as reinforcement within an epoxy matrix. Variations of PKS addition were set at 12 wt.%, 20 wt.%, and 24 wt.%. Flexural test results indicated that PKS addition significantly influenced flexural strength, with the highest value (169.67 MPa) observed in specimen A3 (12 wt.% PKS) and the lowest (58.74 MPa) in specimen A1 (24 wt.% PKS). Shore D hardness testing revealed a complex trend: specimen A4 (30% fiberglass) exhibited the highest hardness, whereas specimen A2 showed the lowest. These findings underscore the importance of balancing fiberglass and PKS proportions to achieve optimal and sustainable mechanical performance.